Continuous microwave excitation of excimer lamps - Hassal, Bradley Scott (My University, 1991)
For decades, microwaves have been used to create gas discharges for many applications. This thesis deals with the use of microwaves to excite gas discharges for incoherent optical sources, with particular emphasis on excimer systems. In addition, microwave excitation of a gas laser is considered. A novel apparatus was designed and built to couple 2.45-GHz microwave radiation into a gas discharge. The microwave resonator is the essential part of this equipment, and a detailed discussion of its design and performance is given. The resonator is characterized both theoretically and experimentally in order to determine the coupling efficiency and peak electric-field strength. Specialized theory is developed in order to evaluate many parameters of a microwave-excited discharge. The phenomenon of skin effect is investigated quantitatively and expressions for the plasma frequency and electron density are developed in terms of collision frequency and observable parameters (e.g., skin depth). Expressions for peak electric-field strength, ionization coefficient and collisionless electron energy are also developed. The results of an extensive investigation of continuous-wave microwave-excited excimer fluorescence are reported. Rare-gas halide, homonuclear halogen and heteronuclear halogen systems are examined and the corresponding ultraviolet spectra are presented. Truly continuous excimer emission has been achieved (for the first time) on several transitions. For systems of particular interest (e.g. XeCl and KrCl), the effects of total pressures and gas composition on fluorescence output are investigated, and the appropriate spectra are presented. Finally, the potential operation of microwave-excited carbon dioxide and argon-ion gas lasers is investigated, and upper limits are deduced for the small-signal gain under various conditions.
Keywords: Engineering Physics; Other Engineering; Other Engineering